2003
DOI: 10.3346/jkms.2003.18.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ylang-Ylang Essential Oil on the Relaxation of Rat Bladder Muscle in vitro and White Rabbit Bladder in vivo

Abstract: Current and primary treatment modality in overactive bladder includes the administration of anticholinergics. The demand for new agents has been rising since anticholinergics have proven to come with many side effects. This study was designed to investigate the effects of ylang-ylang essential oil (YYEO) on the relaxation of urinary bladder muscle in vitro and in vivo. Effects of YYEO were assessed on resting tension, and electrical field stimulation- and various drug-induced contraction in vitro by checking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…f. & Thomson) has been found to cause a decrease in blood pressure and pulse rate and increase attentiveness and alertness in humansgeneral "harmonization" after either inhalation [36] or transdermal absorption [37]. Ylang-ylang oil has also shown in vitro and in vivo urinary bladder muscle relaxant effects [38]. floral essential oil), for example, has been found to reduce anxiety in post cardiac surgery patients [43].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…f. & Thomson) has been found to cause a decrease in blood pressure and pulse rate and increase attentiveness and alertness in humansgeneral "harmonization" after either inhalation [36] or transdermal absorption [37]. Ylang-ylang oil has also shown in vitro and in vivo urinary bladder muscle relaxant effects [38]. floral essential oil), for example, has been found to reduce anxiety in post cardiac surgery patients [43].…”
mentioning
confidence: 99%
“…Ylang-ylang oil has also shown in vitro and in vivo urinary bladder muscle relaxant effects[38]. The major components of ylang-ylang oil are linalool (15-28%),…”
mentioning
confidence: 99%
“…While several studies confirmed the antispasmodic effect of essential oils extracted from common vegetal species extensively used in Asia or Europe like Cananga odorata [10], Foeniculum vulgare [18] or Artemisia dracunculus [21], other studies showed significant spasmolytic effects of essential oils from less-known plant species like Xylopia langsdorffiana [12], Ferula heuffelii [17] or Hofmeisteria schaffneri [24], proving that new natural sources of bioactive molecules are constantly being discovered.…”
Section: Resultsmentioning
confidence: 99%
“…Other isolated organs used for the evaluation of antispasmodic effect were rabbit jejunum, rat ileum, bladder or uterus and sheep ruminal and abomasal muscles. An experimental model used in vitro cell cultures [15] and only two experiments used in vivo techniques: rabbit bladder in vivo and gastrointestinal transit test in mouse [10,24]. The ex vivo techniques are predominant due to their use without the limitations of drug bioavailability which may be a problematic issue for the in vivo models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation